Mypes and sustainability in times of pandemic in Arequipa, Perú: An structural equation model - Velasquez Chacon, Erika (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The objective of the study is to develop a structural equation model (SEM) to evaluate levels of sustainability of MSEs in times of pandemic, based on confirmatory factor analysis (CFA) and exploratory factor analysis (EFA), where six constructs oriented to integrated practices and aspects of sustainable development are analyzed, As a result of the study, the correlation between integrated practices and the pillars of sustainability that lead to the improvement of the management of MSEs and their capacity for adaptability in the face of complex contexts is evident, here equality and opportunity are essential in business development.